A carta/letra entre Derrida e Lacan - Kaio Adriano Batista Fidelis (2018)
Following the hypothesis that the mismatch between Jacques Derrida and Jacques Lacan provides a possible opening of thought and critics, we analyze the debate between these two authors on the destiny of the letter in Edgar Allan Poes The Purloined Letter. Starting from the Lacanian assertion a letter always arrives at its destination (Lacan, 1957/1999, p. 45, translation by the authors), Derrida (1975/2007) analyzes the Lacanian conclusions, pointing to a truth theory, where the signifier phallus takes place as a transcendental signifier, in a way that the literary analysis of this story would be entirely impregnated by this notion. Derrida will point yet to the possibilities of detour and destructibility of the letter/letter apparently refused by Lacan, inscribing in its itinerary, therefore, an aporia of undecidability. With the purpose of extracting the irreducible between these two conceptions, we use Derridas analysis of the Lacanian text to point there what, despite of the philosophical critic, plays a role in Lacans clinical concern. In this regard, we demonstrate through a journey into the texts by Lacan how the notion of letter develops itself with literature as indispensable company. We believe that this notion functions as a reading operator in the literature as well as in the Clinic, keeping the openness of the text and of the unconscious as converging operations.